Design Of An Application For Managing Educational Donation Funds At A School In Bandung - Mustikwati, Rhieke; Marjito, Marjito; Rohpandi, Dani; Damayanti, Resti Aulia (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
The collection of payment data and the recording of expenses are essential activities in financial management for both individuals and organisations. In the ever-evolving realm of information technology, creating a web application serves as an effective means to streamline and improve the efficiency of these procedures. The web application can leverage technology to offer capabilities that enhance the collection of payment data. Users can digitally document payments, set payment reminders, and efficiently track their payment history. The creation of a technology-driven online application for gathering payment data and tracking spending provides convenience for users while also benefiting organisations or enterprises. Organisations can analyse expenditure patterns, optimise resource allocation, and enhance decision-making in financial planning with well-documented data.